Células tronco mononucleares autólogas na cicatrização de defeitos tibiais agudos experimentais de cão - Oliveira, Graziela Kopinits de (2008)
This research was aimed at evaluating the mononuclear stem cells (MSC) use in experimental bone defect healing, as an alternative to the conventional methods, analyzing the healing speed, and the presence of these cells in the new-born tissue. The bone marrow (BM) was collected from 18 dogs, counted and morphometrically analyzed, through manual count and myelogram. The dogs were separated in three groups (G1, G2, G3) of six animals. A surgical tibial bone defect was made then, in each dog and the wound was treated with gelatin sponge and physiologic solution (G1), gelatin sponge and processed bone marrow (G2) and gelatin sponge, processed BM and morphogenetic bone protein (G3). The healing was then evaluated through radiographic study and the presence of MSC was identified through Qtracker nanocrystal labeler and fluorescent light microscopy one week after the surgery. Cells from the bone lineage were found among the labeled cells. The radiographic evaluations demonstrate speeding in bone growth in the groups G2 and G3, and were significant statistically differences between the G1 and G3 in all studied periods and between G1 and G2 at the 30 and 45 days period. The supplemented or not-supplemented with rhBMP-2 adult mononuclear stem cells use are favorable alternatives to the speed the healing process of acute dog tibial experimental defects.